"It's a Story of Another World": Perceptions of the Tokyo 2020 Paralympic Games Among Japanese Athletes With Psychiatric Impairments - Akimoto, Shigeharu; Nagata, Shinichi; Richardson, Emma V (Adapted physical activity quarterly, 2025)
This study explored how athletes with psychiatric impairment in Japan perceived the Tokyo 2020 Paralympic Games. Data from 15 interviews were analyzed using reflexive thematic analysis; consequently, three themes were generated: (1) The Paralympics: "A Story of Another World"-the participants viewed the Paralympics only as a movement and not directly related to them; (2) "Do I Really Have to Work That Hard?"-"supercrip" representations through the Paralympics led to the disempowerment and disablement of people with psychiatric impairment, exacerbating their symptoms; (3) "A Futsal That Really Isn't Very Good"-the privileged status of the Paralympics presents only a facet of disability sport, which has resulted in other sports for people with psychiatric impairment, such as football, not being properly valued. This study adds to the literature regarding the legacy of the Paralympics and emphasizes moving beyond using the Paralympics as a vehicle for a more inclusive world.